Factors associated with influenza vaccination among adult cancer patients: a case–control study. (10th April 2014) - Vinograd, I.; Baslo, R.; Eliakim‐Raz, N.; Farbman, L.; Taha, A.; Sakhnini, A.; Lador, A.; Stemmer, S. M.; Gafter‐Gvili, A.; Fraser, D.; Leibovici, L.; Paul, M.; et al.
Abstract Influenza vaccination is recommended for cancer patients; however, adherence is low. We aimed to identify predictive factors for vaccination among cancer patients. We conducted a case–control analysis of a patient cohort in the 2010–2011 influenza season. We included adult cancer patients with solid malignancies undergoing chemotherapy, and haematological patients with active disease. Patients who died between October and November 2010 (N = 43) were excluded from analysis. Cases received the 2011 seasonal influenza vaccine, and controls did not. Data were obtained from patients' records, and validated through personal interviews. We collected socio‐demographic information, and data on the malignancy and co‐morbidities and triggers for vaccination and non‐vaccination. We performed bivariate and multivariable analyses, in which vaccination status was the dependent variable. Of 806 patients included in analysis, 387 (48%) were vaccinated. Variables associated with vaccination on bivariate analysis were older age, higher socio‐economic status, lower crowding index, marital status (widowed > married > single), malignancy type (haematological > solid tumours) and time from diagnosis, low‐risk malignancy, diabetes, past vaccination, country of birth (non‐Russian origin), and physicians' recommendations. Predictive factors found to be independently associated with vaccination on multivariable analysis were past vaccinations, low‐risk malignancy, and country of birth. In the analysis conducted among interviewees (N = 561), recommendations from the oncologist (OR 10.7, 95% CI 5.4–21.2) and from the primary‐care physician (OR 3.35, 95% CI 2.05–5.49) were strong predictors for vaccination. We conclude that 'habitual vaccinees' continue influenza vaccinations when ill with cancer. Physicians' recommendations, especially the oncologist's, have a major influence on patients' compliance with influenza vaccination.